Homozygous SMN1 gene deletion as a cause of intrauterine and neonatal mortality - Ghulam Ali, Parisa Batul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Deoxyribonucleic acid is not only responsible for normal functioning and metabolism of body by the formation of essential proteins which are responsible for individuals growth and development but it is also responsible for transferring traits & genetic disorders from parents to their offspring, either these genetic traits make them carriers or major diseased individual, these conditions may arise because of any false nucleotide base insertion, or nucleotide deletion or any gene replacement due to radiations or mutations. SMA (survival motor atrophy) is a condition that arises because of less production or unavailability of the SMN protein, which is synthesized by the SMN-1 gene. A case of 29 years old married woman (cousin marriage- Consanguinity) has been discussed, she lost her 4 babies after birth (neonatal deaths) in between the duration of 2 to 8 months, with one intrauterine miscarriage (intra-uterine death), after CVS it was found that SMN-1 was absent in the genetic makeup of her all babies, and they were not able to survive because of muscular atrophy in pulmonary muscles causing pulmonary distress and reduced body movements with edematous condition and other body organ failures including kidney and liver. It was concluded that SMN-1 gene absence is not only responsible for causing intrauterine, neonatal deaths but also causes sudden deaths in adult age suddenly by causing paralysis. Gene replacement therapies with other oligonucleotides and splicing modifiers have been introduced with the advancement of biotechnology for the treatment of SMA disease.